Chão de meninos : o espaço literário na narrativa memorialista de Zélia Gattai - Rocha, Ramon Diego Câmara (2018)
The research in relief seeks to analyze, through the book Boys floor, by the Bahian author Zélia Gattai, how the interiorization of the fictional universe, supported by an aesthetic treatment with language, generated spaces of frontier between literature and the autobiographical genre, reflecting on the space of the literary in the compositional universe of his narrative. For this, we will divide our reflections into three integrated parts that will constitute the whole of our thinking. In the first chapter, entitled “The hybridizations of literary space”, we try to demonstrate not only the importance of literature as the guardian of the unsaid, but also the creation of a literary space at the heart of the autobiographical text, expanding the limits of aesthetic composition and reflecting on certain institutional frameworks, as much of the autobiographical text, as of the literary one. In this direction, and using the theoretical framework of philosophy and literary theory, we will support authors who have studied this subject, such as Phillippe Lejeune, Pierre Bourdieu and Leonor Arfuch. As for the study of these texts, we will take as a methodology a hermeneutic-phenomenological approach of this space of creation, dialoguing with authors such as Maurice Blanchot, Hans George Gadamer, Gaston Bachelard, Martin Heidegger and others. Even in this first moment of our questions, we will also see how the reorganization of the mnemonic occurred in literature, especially in Brazilian literature. In this context, authors such as Alfredo Bosi and Antonio Candido will also serve as a basis for reflect on certain aspects of memorialism in our literature. In the second chapter, entitled “The literary space and the memoirist narrative of Zélia Gattai”, it will be debated how some memorialist productions in Brazil, giving emphasis to the one of the Bahian writer, constructed a literary space at the core of its verbal expression, through a treatment aesthetic of lived. Here we shall begin to remember as a matter of our perception of the world, tied to an aesthetic-spatial construction of the narrated. For a better understanding of this compositional disposition we will avail ourselves of this construction of the literary space from the mnemonic through authors like Henri Bergson, Benedito Nunes, Beatriz Sarlo, Antonio Cândido, Luiz Costa Lima, among others. Already in the third and final chapter, “Stepping on a boys floor”, we will see how the literary space in the narrative of boys floor manifests, focusing more emphatically on the work of Zélia and evidencing its narrative composition in a frontier aesthetic, between the literary and the autobiographical through the spatialization of their memories within their verbal expression. In this sense, authors such as Luís Alberto Brandão, Henri Bergson, Gaston Bachelard and Paul de Man will be importants in this journey.